2014
DOI: 10.3109/09513590.2014.981803
|View full text |Cite
|
Sign up to set email alerts
|

Does progesterone supplementation improve pregnancy rates in clomiphene citrate and intrauterine insemination treatment cycles?

Abstract: Luteal phase progesterone supplementation in CC-IUI cycles can improve endometrial receptivity as judged by the improved clinical pregnancy rates as the primary outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The study resulted in an increase of clinical pregnancy rate in the CC + EE group (29 % vs 10 %, p = 0.02) even if there was no statistically significant difference in the ongoing pregnancy rate between the two groups [ 48 ]. However, an interesting recent retrospective cohort analysis revealed that luteal phase progesterone supplementation in CC-IUI cycles can improve endometrial receptivity with an effect closely related to the endometrial thickness [ 49 ]. Patients who appeared to receive the greatest benefit of progesterone supplementation had an endometrial thickness of 6–8 mm; their clinical pregnancy rate was found to be improved two-fold (OR 2.04; 95 % CI 1.01 to 4.14) [ 49 ].…”
Section: Non-gonadotropin Induced Ovulatory Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study resulted in an increase of clinical pregnancy rate in the CC + EE group (29 % vs 10 %, p = 0.02) even if there was no statistically significant difference in the ongoing pregnancy rate between the two groups [ 48 ]. However, an interesting recent retrospective cohort analysis revealed that luteal phase progesterone supplementation in CC-IUI cycles can improve endometrial receptivity with an effect closely related to the endometrial thickness [ 49 ]. Patients who appeared to receive the greatest benefit of progesterone supplementation had an endometrial thickness of 6–8 mm; their clinical pregnancy rate was found to be improved two-fold (OR 2.04; 95 % CI 1.01 to 4.14) [ 49 ].…”
Section: Non-gonadotropin Induced Ovulatory Cyclesmentioning
confidence: 99%
“…However, an interesting recent retrospective cohort analysis revealed that luteal phase progesterone supplementation in CC-IUI cycles can improve endometrial receptivity with an effect closely related to the endometrial thickness [ 49 ]. Patients who appeared to receive the greatest benefit of progesterone supplementation had an endometrial thickness of 6–8 mm; their clinical pregnancy rate was found to be improved two-fold (OR 2.04; 95 % CI 1.01 to 4.14) [ 49 ]. These patients seem to have an endometrium still receptive to progesterone administration, whereas patients with an endometrial thickness less than 6 mm are not responsive to progesterone supplementation for CC-related receptors depletion/inhibition and patients with an endometrial thickness greater than 8 mm represent a group with good reproductive prognosis in which progesterone supplementation is unable to provide further reproductive improvement.…”
Section: Non-gonadotropin Induced Ovulatory Cyclesmentioning
confidence: 99%
“…In the final analysis, 105 eligible studies (19 prospective and 86 retrospective cohort studies) were included, involving more than 271,632 pregnant women (Figure 1). 14,15,28–130 The main characteristics of included studies were summarized in Table S1. In total, 100 studies reported the association between maternal BMI and CPR among pregnant women undergoing ART, among which 53 reported MR and 51 reported LBR (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 100 studies reported the association between maternal prepregnancy body weight and CPR after ART 14,15,28–55,58–80,82–117,119–122,124–130 . At per‐woman level, 54 studies, involving 109,688 pregnant women, showed an inverted J‐shaped relationship between maternal BMI and CPR ( P n < 0.01) 14,28–31,34–36,40,41,44,46,47,49,53,58,60,61,64–68,75,76,78,82,85,86,88–95,97,99,103–106,109,112–114,119,121,124,126–128,130 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation